ANALYSIS OF PHONOLOGICAL ERRORS IN CONSONANT /-t/ AND /-d/ BY ENGLISH TEACHERS IN INDONESIA - Novy Dwi Shaphitri; Evi Jovita Putri; Tri Rahayu (PROJECT (Professional Journal of English Education), 2022)
The phonological errors have received a lot of attention in consonant /-t/ and /-d/ at the final position by English teachers in Indonesia, they have an important role to guide students in practicing English actively and correctly. The teachers however have trouble in pronouncing words that are found to have the suffix -ed as the past or part participle words.This paper aims to see the accuracy of English consonant blends at the final position and want to see the causes of the error by English teacher by applying PRAAT. This study uses a descriptive qualitative method. For the participants, the writers choose 8 English teachers from random levels. The samples are one Javanese person and seven Jakarta people (two males and six females). The result of this research three teachers pronounce 57%  almost the same as native speakers, one teacher pronounce 50 % almost the same as native speakers, three teachers pronounce 36% almost the same as native speakers, and the last two teachers pronounce 14% accuracy when compared to native speakers. The results of this study support people’s assumptions about phonological errors in producing alveolar sounds. It is found that the teachers are generally influenced by their first language, Indonesian. Then they tend to have a  less consideration at the proper pronunciation. Keywords:  Phonological Error, Alveolar Sounds, PRAAT